White LEDs with limit luminous efficacy; AIP Conference Proceedings; Vol. 1698 : Advanced Materials in Technology and Construction, AMTC-2015 - Lisitsyn V. M. Viktor Mikhailovich; Lukash V. S. Vitaly Sergeevich; Stepanov S. A. Sergey Aleksandrovich; Ju Yanyan (2016, 2016)
Title screen